Financial Literacy and Decision Making Among Women In India - Dhaigude, Rahul (The journal of contemporary issues in business and government, 2021)
Financial Literacy level across various nations has substantial effects on how the decisions are taken, and research has shown that financial illiteracy is widespread among various developed countries and even worse in developing countries. This paper seeks to understand the relationship and the impact of level of financial literacy on the household decision making of the urban working population residing in cities in a developing country like India. The research paper will also take into account the determinant that largely, is the prime factor of the study i.e. gender gap that prevails by establishing the correlation between the two factors. Household savings and investment are significantly affected by how decision-making power is allocated between women and men. In particular, when intra-household financial decisions are made by women, savings and investment are often greater and repayment of debt is more likely. A detailed analysis will be carried out on the factors affecting and evaluate the association between the gender stereotypes and the gap that exists. The paper would also throw light on the current level of financial literacy that exists between the two genders and then estabilish a correlation between gender gap and financial literacy level in the area subject to be researched upon.